Beyond quotas: Women’s substantive participation and democratic consolidation in Timor-Leste - Felisberto de Carvalho; Raden Roro Nanik Setyowati (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Women's political participation in post-conflict states presents a persistent paradox: numerical gains in representation rarely translate into substantive policy influence. Focusing on Timor-Leste, where quota legislation elevated women's parliamentary representation to 38% by 2023, this study examines the structural, institutional, and sociocultural conditions that mediate the conversion of descriptive into substantive representation. A systematic literature review (2015–2025), conducted following PRISMA 2020 guidelines and synthesising peer-reviewed studies, institutional reports, and policy documents, frames the analysis through critical actor theory, feminist institutionalism, and intersectionality. Findings reveal that patriarchal norms, elite gatekeeping, institutional fragility, and gender-based political violence collectively constrain women's policy agency despite formal numerical gains. Conversely, coalition-building, gender-responsive budgeting, leadership development, and anti-violence mechanisms emerge as critical enablers for translating presence into influence. Substantive women's participation is further shown to advance democratic consolidation by broadening accountability and enhancing institutional legitimacy in fragile state contexts. Comparative analysis of Rwanda and Nepal affirms that quota-driven reform must be accompanied by cultural transformation to yield durable outcomes. The study contributes theoretically by advancing integrated gender-governance frameworks, empirically by situating Timor-Leste within comparative post-conflict scholarship, and normatively by generating recommendations aligned with SDG 5, SDG 16, and ASEAN gender frameworks. Sustainable democratic governance ultimately requires moving beyond formal quotas towards structural and cultural change that secures women's substantive empowerment.